Exsolution effects in CO2 huff-n-puff enhanced oil recovery: Water-Oil-CO2 three phase flow visualization and measurements by micro-PIV in micromodel. (October 2021) - Lu, Haowei; Huang, Feng; Jiang, Peixue; Xu, Ruina
Highlights: Developed high-temperature and high-pressure micro-PIV and fluorescence visualization system. Simultaneously measured the velocity and phase distribution of water-oil-CO2 phases. CO2 exsolution induced three-phase flow behavior various under different wettability. Observed thin water film flow beneath oil or CO2 phase on water-wet solid surface. Aqueous phase could invade and drive residual oil phase flow downstream in oil-wet solid surface. Abstract: CO2 huff-n-puff is one of the most important methods to enhanced oil recovery, which can simultaneously improve oil production and achieve CO2 geological storage. Due to the fluctuation of formation pressure, water-oil-CO2 three phase migration in porous structures was affected significantly by supercritical CO2 exsolution and expansion. However, the existing research on phase distribution is not enough to understand the mechanism of three-phase migration and the essential processes beneath the phase distribution are still not clear. Here, we developed a high-temperature and high-pressure micro-PIV (Particle Image Velocimetry) and fluorescence visualization experimental system (10 MPa, 50°C), which realized the simultaneous measurement of the velocity field and phase distribution of the water-oil-CO2 three-phase. The multiphase migration process under different wettability conditions during the supercritical-subcritical CO2 exsolution were captured. The results showed that the exsolution induced CO2 bubbles expansion in aqueous and oil phase blocked the preferential migration passage and dominated different multiphase migration mechanisms under different wettability. It was found that in water-wet condition, the aqueous phase can still migrate downstream through the water film between the CO2 /oil and the wall, unable to further drive CO2 /oil downstream. While in oil-wet condition, the aqueous phase eventually broke through the oil phase blocked at throats and formed a new preferential migration passage, pushing part of the oil phase encapsulating CO2 bubbles downstream. Our research reveals the multiphase migration mechanism beneath the phase distribution under different wettability during the exsolution process of the huff-n-puff, which provides a new insight for CO2 enhanced oil recovery and geological storage.